A Study On Sthoulya And Its Management By Certain Drugs With The Principle Of Treatment – “Guru Chaatarpanam Chestam” - Sethi, Madhusmita Rani; Das, Arun Kumar; Sahoo, Manoj Kumar (International Research Journal of Ayurveda & Yoga, 2021)
In the present era due to the climatic changes and behavioral changes of the human being, westernization of the food, sedentary lifestyle and also due to lack of exercise and various stress factors the “Sthoulya” (Obesity) is being common worldwide both in developed and developing countries. Obesity has negative impact on health & quality of life. Obesity is considered the world’s oldest metabolic disorder. It is common among those who consume Excessive kapha medo vardhaka Ahara and Vihara (diet and regimen). Sthoulya (Obesity) is such a disease which provides a platform for so many hazards like hypertension, coronary heart disease, diabetes mellitus, osteoarthritis, as well as psychological disorders like stress, anxiety, depression and certain types of cancer. These diseases are definitely associated with an increased risk of mortality. Looking upon the severity of this disorder the principle of treatment of Sthoulya advocated by Maharishi Charak i.e. “GURUCHA ATARPANA CHESTAM”.On the basis of this Principle certain drugs were taken and prepared a compound form i.e. Haritaki Pippali Madhu Yoga as a remedy for disease Sthoulya. The patients were administered Haritaki Pippali Churna 5 gm with adequate quantity of Madhu twice daily in empty stomach for a period of60 days for Group A. For Group B 500mg placebo capsule twice daily in empty stomach for 60 days. During the present clinical study, it was observed that change in body weight and reducing the sign & symptoms under the trial group patients is significant. Whereas in case of control group patients, it is not significant. The Haritaki Pippali Madhu Yoga has a significant role in the management of Sthoulya and justifies the treatment principle “GURU CHAATARPANAM CHESTAM”. No side effects or with drawl effects were observed.